IMPACT OF SIDE BARRIER ON ROAD SERVICE LEVELS CASE STUDY: INTERSECTION UNSIGNALIZED RAJAGALUH - Rio Refelino Ginting; Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2024)
Majalengka is one of the cities in West Java impacted by the rapid growth of private vehicle numbers. One place in Majalengka that often experiences traffic congestion is the intersection of three markets and the terminal in Rajagaluh. This road connects to Cirebon and tourist areas in the Sindangwangi District. This happens for several reasons, including the significant number of side obstacles along the road around the intersection. Side obstacles at this intersection include street vendors, parked/stopped vehicles, and pedestrians. This research aims to determine the road service level through field surveys at the junction of the three markets and the Rajagaluh terminal. The research methodology employed in this study is qualitative. The use of this qualitative method is interrelated, involving data collection, data grouping, data validation, and finally, data analysis, allowing the emergence of new theories and insights. This research was conducted at the unsignalized intersection near Rajagaluh Market and Terminal in Majalengka Regency. This unsignalized intersection is a junction for inter-district routes located near the terminal and market. Based on the table above, it is found that in the northbound direction, the level of road service is average during the morning and afternoon, while it is classified as high during the evening. In the westbound direction, the level of road service is mild during the morning and afternoon, and during the evening, it is classified as high. The road service level in the eastbound direction is similar, average during the morning and afternoon, and increased during the evening. Therefore, according to the author, the government must improve to anticipate the high traffic volume that will lead to congestion in the future. Based on the study, side obstacles are still relatively low to average. However, this does not mean it will be a benchmark in the future. It is possible that in the coming years, these side obstacles will increase, leading to congestion.